Relationship of Knowledge Levels with the Preparedness Abilities in Dealing with Earthquake Disasters - Retno Yuli Hastuti; Fitriana Noor Khayati; Vita Marta Fatimah (GLOBAL HEALTH SCIENCE GROUP, 2020)
The importance of the knowledge of disaster preparedness can be done early through a disaster alert program if children in particular youth can understand how to save themselves during a disaster. SMP Negeri 1 Gantiwarno had been hit by the 2006-magnitude tectonic earthquake on a 5.9 Richter scale so that the teaching and learning process in class was interrupted by the earthquake. The socialization or simulation of disaster preparedness in the school itself is still rare. The purpose of this study was to determine the relationship between the level of knowledge and the preparedness ability of SMP Negeri 1 Gantiwarno in facing earthquake disasters. This type of research is non-experimental quantitative. This study used a cross-sectional approach which was done on July 8th -14th. The population in this study were 224 students of VIII grade class at SMP Negeri 1 Gantiwarno, Klaten city, Central Java Province, Indonesia. The sample used in this study were 143 grade VIII students of SMP Negeri 1 Gantiwarno. Data collection was performed by visiting groups of students at school. The spearman rank test was done in the statistical testing of this study. The results showed P value of less than α of 0.05, so that there was a relationship between the level of knowledge and ability with the readiness of students of SMP Negeri 1 Gantiwarno. Based on the results, it can be concluded that there is a relationship between the level of knowledge and ability with preparedness in dealing with earthquake in SMP Negeri 1 Gantiwarno.